Age-related Decline in Natural IgM Function: Diversification and Selection of the B-1a Cell Pool with Age - Holodick, Nichol E. (J Immunol, 2016)
Streptococcus pneumoniae is the most common cause of pneumonia, which claims the lives of people over the age of 65 seven times more frequently than those aged 5–49. B-1a cells provide immediate and essential protection from S. pneumoniae through production of natural immunoglobulin, which has minimal insertion of N-region additions added by the enzyme TdT. In experiments with SCID mice infected with S. pneumoniae, we found passive transfer of IgG-depleted serum from aged (18–24-month old) mice had no effect whereas IgG-depleted serum from young (3-month old) mice was protective. This suggests protective natural IgM changes with age. Using single cell PCR we found N-region addition, which is initially low in fetal-derived B-1a cell IgM developing in the absence of TdT, increased in 7–24-month old mice as compared to 3-month old mice. To determine the mechanism responsible for the age related change in B-1a cell IgM, we established a mixed chimera system in which mice were reconstituted with allotype-marked mature peritoneal B-1a cells and adult bone marrow (BM) cells. We demonstrated even in the presence of mature peritoneal B-1a cells, adult BM contributed to the mature B-1a cell pool. More importantly, using this system we found over a 10-month period peritoneal B-1a cell IgM changed, showing the number of cells lacking N-region additions at both junctions fell from 49% to 29% of sequences. These results strongly suggest selection-induced skewing alters B-1a cell derived natural antibody, which may in turn be responsible for the loss of natural IgM-mediated protection against pneumococcal infection.